Loving and Hating Brands: Multiple Relationships between Consumers and Brands - Loureiro, S. M. C. (Handbook of Research on Managing and Influencing Consumer Behavior, 2015)
Since the 90’s of 20th Century brand has been analyzed using the anthropomorphic metaphor. Consumers develop relationships with diverse brands regarding brands as partners. Brands are viewed by customers as symbolic meanings and social and cultural value, which is beyond the utilitarian benefits. Therefore, the purpose of this chapter is to show an overview of the research on consumer-brand relationship (CBR) and presents a theoretical model of consumer-brand relationship process, giving insights for good and bad relationships. The chapter begins with the origin and evolution of CBR. Then, an overview of main theories and the seminal models are shown. Finally, a model of consumer-brand relationship process through good and bad relationships is proposed, and insights for further research are provided.